A study on the factors effecting loan demand in Malaysia’s commercial bank / Nazrul Hanis Zaidan - Zaidan, Nazrul Hanis (Faculty of Business and Management, 2011)
This paper studies the factors that affect Malaysia commercial bank loan demand. Using SPSS 17.0 and Multiple Linear Regressions, the study identifies the relationship between GDP, interest rates and inflation rate with loan demand of Malaysia commercial bank. Using quarterly 10 years total loans applied for Malaysia commercial bank, GDP, BLR and CPI from 2000 to 2010 data taken from BNM, the relationship implies that GDP and Inflation are positively related to loan demand and interest rate is negatively related with the loan demand consistent with the previous research done before. The findings in this investigation are useful for future researchers, the economists and financial institutions who are concerned with the lending decisions in Malaysia’s commercial bank.